2020
DOI: 10.1039/d0tc02403a
|View full text |Cite
|
Sign up to set email alerts
|

Mode cleaning in graphene oxide-doped polymeric whispering gallery mode microresonators

Abstract: The physical mechanisms behind a mode cleaning effect observed in graphene oxide (GO)-doped polymeric microresonators are uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Several polymeric formulations have been employed as photoresists, such as acrylic [ 51 , 135 ] and epoxy resins [ 130 , 132 ], and various materials have been incorporated into them to meet specific applications. Polymeric microresonators fabricated by TPP have been incorporated with organic dyes to realize optically active microdevices [ 125 , 130 , 134 ], with liquid crystal networks to confer elasticity for optical tunability [ 131 , 136 ], and with nanodiamonds to enable quantum photonics applications [ 135 ], among other materials [ 137 ].…”
Section: Devices Fabricated Via Tpp: General Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several polymeric formulations have been employed as photoresists, such as acrylic [ 51 , 135 ] and epoxy resins [ 130 , 132 ], and various materials have been incorporated into them to meet specific applications. Polymeric microresonators fabricated by TPP have been incorporated with organic dyes to realize optically active microdevices [ 125 , 130 , 134 ], with liquid crystal networks to confer elasticity for optical tunability [ 131 , 136 ], and with nanodiamonds to enable quantum photonics applications [ 135 ], among other materials [ 137 ].…”
Section: Devices Fabricated Via Tpp: General Applicationsmentioning
confidence: 99%
“…One proposed solution to achieve mode cleaning is by incorporating a lossy element in a low concentration into the microresonator. It was shown that the incorporation of graphene oxide (GO) to WGM microresonators led to the suppression of a number of resonances in the spectrum without significantly reducing the Q-factor of the most prominent resonances [ 137 ]. Another route to mode cleaning is by decreasing the microresonator diameter to a few microns [ 149 ].…”
Section: Devices Fabricated Via Tpp: General Applicationsmentioning
confidence: 99%
“…It has been used to create a variety of optical structures for applications in many fields, such as photonic crystals [ 18 ], waveguides [ 19 ], resonators [ 20 ], and microneedles [ 21 ]. One of the main advantages of the 2PP technique is that it is relatively simple to incorporate dopants into the photoresist [ 22 ], making 2PP an appropriate method to fabricate functional structures, such as nanotube-doped structures [ 23 ], rhodamine-doped, and graphene oxide-doped microresonators [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[97][98] This way, our numerical model is now able to simulate third-order nonlinear absorption, besides nonlinear refraction. This feature is particularly interesting to characterize semiconductor waveguides, 95 dye-doped polymer waveguides [88][89] or graphene-doped structures, 31,86 where nonlinear absorption plays an important role.…”
Section: Equation 37 Was Modified To Include Two-photon Absorption As Followsmentioning
confidence: 99%
“…19 When it comes to photonic applications, structures like microresonators, interferometers and waveguides, [20][21][22] microlenses, 23 fiber-to-chip couplers, 24 photonic crystals, 25 among others have been fabricated. Another great advantage of DLW in polymeric materials is the ease of incorporation of different doping materials to the polymeric matrices, like organic dyes, [26][27][28] metal nanoparticles and quantum dots, 29 graphene-based materials, [30][31] etc. This feature allows the modification of the material physical properties, allowing for the fabrication of devices with specific properties.…”
Section: Introductionmentioning
confidence: 99%